Pengaruh Degradasi Agregat Terhadap Karakteristik Campuran Beraspal - Putra, Mohd. Denny Yudha; Putra, Sasana; Irsan, Mulyadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
Gradation indicated has a considerable influence on interlocking which will subsequently affect the carrying capacity / stability. Therefore, the research was conducted with the aim to know the extent of the effect of aggregate degradation on the asphalt mixture quality decline. In this research, laboratory testing is done by taking asphalt samples at 2 Asphalt Mixing Plant (AMP) and different onsite location. Furthermore, as secondary data obtained Job Mix Formula on each AMP. After obtaining asphalt samples and Job Mix Formula, laboratory testing is conducted to determine the level of aggregate degradation of the asphalt quality decline. In laboratory test for asphalt samples of PT.Manggung Polah Raya obtained a crude aggregate fraction of 4,35%, a fine aggregate fraction of 6,23%, and a filler fraction of 1,87% indicated the higher gradation change becomes smoother. The value of mixed characteristics produced on Marhsall Test according to DGH specification 2010 for density > 2gr / cc, VMA > 15%, VIM 3,5%-5%, Flow > 3mm, And Stability > 800Kg. From the test result of asphalt samples of PT.Rindang Tigasatu Pratama obtained a crude aggregate fraction of 0,98%, a fine aggregate fraction of 0,12%, and a filler fraction of 0,86% indicating gradation increasingly coarse.Keywords: Gradation, Interlocking, Asphalt Mixing Plant (AMP) Marshall Test, Office of Highway 2010 Specification.